Maternal health care utilization following the implementation of the free maternal health care policy in Ghana: analysis of Ghana demographic and health surveys 2008-2014 - John Azaare; Gifty Apiung Aninanya; Kasim Abdulai; Francis Adane; Robert Bagngmen Bio; Martin Hushie (BMC, 2024)
Abstract Background In July 2008, Ghana introduced a 'free' maternal health care policy (FMHCP) through the national health insurance scheme (NHIS) to provide comprehensive antenatal, delivery and post-natal care services to pregnant women. In this study, we evaluated the 'free' policy impact on antenatal care uptake and facility-level delivery utilization since the policy inception. Methods The study used two rounds of repeated cross-sectional data from the Ghana Demographic and Health Survey (GDHS, 2008-2014) and constructed exposure variable of the FMHCP using mothers' national health insurance status as a proxy variable and another group of mothers who did not subscribe to the policy. We then generated the propensity scores of the two groups, ex-post, and matched them to determine the impact of the 'free' maternal health care policy as an intervention on antenatal care uptake and facility-level delivery utilization, using probit and logit models. Results Antenatal care uptake and facility-level delivery utilization increased by 8 and 13 percentage points difference, observed coefficients; 0.08; CI: 95% [0.06-0.10]; p < 0.001 and 0.13; CI: 95% [0.11-0.15], p < 0.001, respectively. Pregnant women were 1.97 times more likely to make four plus [a WHO recommended number of visits at the time] antenatal care visits and 1.87 times more likely to give birth in a health care facility of any level in Ghana between 2008 and 2104; aOR = 1.97; CI: 95% [1.61-2.4]; p < 0.001 and aOR = 1.87; CI: 95% [1.57-2.23]; p < 0.001, respectively. Conclusions Antenatal care uptake and facility-level delivery utilization improved significantly in Ghana indicating a positive impact of the FMHCP on maternal health care utilization in Ghana since its implementation.